Analysis of Medan Community Perceptions Regarding Program Implementation and Service Quality of BPJSTK Medan City Branch - Mega Nova Eliza Manullang; Jihan kamila; Alnafis Hasibuan; Elias Dion Pasaribu (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the perceptions of the people of Medan City regarding the implementation of programs and service quality of the Medan City Branch of the Social Security Administration Agency for Employment (BPJSTK). Although social security is a fundamental pillar for worker protection, the implementation of programs, including those organized by BPJSTK, still faces challenges such as suboptimal service quality and participant dissatisfaction. Specifically in Medan, obstacles include bureaucratic inefficiency, procedural complexity, and suboptimal use of information systems. This qualitative study uses in-depth interviews with the community and BPJSTK employees, as well as analyzing data using the Miles and Huberman model (data reduction, data presentation, and conclusion drawing/verification). The results of the study show that the services provided by the BPJSTK Medan Kota Branch are fairly well organized, but still have shortcomings. The complexity of the program is most felt in the claim requirements, changes in provisions, and technical terms that are difficult to understand (such as the online JMO application), which is exacerbated by the lack of official socialization that reaches all groups. Although the officers are considered quite knowledgeable and empathetic, the speed of service promises (disbursement time) and consistency of online responsiveness are not yet uniform. The public hopes that BPJSTK will improve the consistency of information, accelerate digital service responses, and ensure that staff provide uniform and accurate explanations. This study provides a holistic contribution by integrating program analysis, service quality (using the ServQual dimensions), participant literacy, and digital service experience.